Optimising amperometric pH sensing in blood samples: an iridium oxide electrode for blood pH sensing - Chaisiwamongkhol, K; Batchelor-Mcauley, C; Compton, R (Royal Society of Chemistry, 2018)
Amperometric pH sensing in blood samples has been studied using iridium oxide electrodes. The iridium oxide electrodes are made by electrodeposition of iridium oxide onto an iridium micro-disc electrode from an alkaline solution of iridium(iii) oxide. The response of the electrode is studied in aqueous solutions and authentic samples of sheep's blood employing both cyclic voltammetry and square wave voltammetry. Uncertainties of pH measurement in blood samples via cyclic voltammetry (±0.07 pH units) were improved by a factor of two using square wave voltammetry (±0.03 pH units). Limitations of amperometric pH sensing in blood samples are considered as caused by the uncertainty of the required reference measurements (via a conventional glass electrode) and also the use of matrix-free and low ionic strength buffers to calibrate a standard glass electrode for the measurement of blood pH.